Pengaruh Brand Ambassador dan Korean Wave Terhadap Minat Beli NCTzen pada Produk Somethinc - Cutisah; Netti Nurlenawati; Dexi Triadinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to investigate the influence of Brand Ambassador and Korean Wave on NCTZen's purchasing interest in Somethinc products. This research is quantitative, with 63.3 thousand NCTzens who are followers of the NCT Dream fan account (yodream25) as the population. The sample size of 96 respondents was calculated using the Cochran formula by applying a non-probability sampling method, purposive sampling type. Data analysis was processed using the path analysis method, with data collection through distributing questionnaires using Google Form. Using data analysis tools with SPSS version 27. The results show that there is a significant positive relationship between Brand Ambassador and the Korean Wave. Apart from that, this research also reveals that Brand Ambassador has a significant influence in influencing NCTzen's buying interest in Somethinc products, the Korean wave phenomenon also influences NCTzen's buying interest in Somethinc products. Meanwhile, Brand Ambassador and Korean Wave simultaneously influence NCTzen's buying interest in Somethinc products.